Participação das fintechs na concessão de crédito no sistema financeiro nacional : uma análise comparativa entre fintechs e bancos tradicionalmente constituídos - Nascimento, Franklin Martins (2023)
This dissertation examines the evolution of Fintechs' involvement in the Brazilian credit concession market from 2019 to 2022, using official data provided by the Central Bank of Brazil (Bacen). The data was collected from Bacen's official website using the SCR system, which encompasses all credit transactions in Brazil authorized by financial institutions. The analysis reveals a notable increase in Fintechs' participation in this market, accompanied by a rise in the number of Fintechs operating in Brazil, extending beyond credit provision to various other sectors.